Purification and biochemical/molecular characterisation of antimicrobial peptides produced by Saccharomyces cerevisiae and evaluation of their mode of action - Branco, Patricia (2019)
Tese apresentada para obtenção do Grau de Doutor em Engenharia Alimentar